Simulation of pedestrian flow with evading and surpassing behavior in a walking passageway. (December 2017) - Jia, Xiaolu; Yue, Hao; Tian, Xin; Yin, Huanhuan
The pedestrian flow with evading and surpassing behavior in a walking passageway is simulated based on a modified social force model in order to explore the influence of this behavior on evacuation efficiency, bottleneck passing capacity, and the macroscopic phenomenon. A pair of conjugated self-driven forces is introduced to enable a pedestrian to avoid a direct collision and keep a normal velocity magnitude while confronting an obstacle. The pedestrian avoiding time is used to define the triggering conditions of evading and surpassing behavior, and has been estimated through practical experiments. Simulation results show that in a passageway without spatial obstacles, the evading and surpassing behavior will increase the evacuation time under the condition that the pedestrian number is larger than a critical value. Moreover, when a spatial obstacle exists, both the rise of pedestrian numbers and the decline of bottleneck width would increase the evacuation time. Meanwhile, it is observed that compared with a bar-shaped obstacle, a circle-shaped obstacle corresponds to a larger bottleneck passing capacity and less evacuation time when the size of the spatial obstacle is above a critical value. In addition, a phenomenon of a triangle "evading region" caused by the evading and surpassing behavior also can be observed before the spatial obstacle through simulation and experiments. Furthermore, it can be concluded that a circle-shaped obstacle corresponds to a stronger guiding function and a larger area of "evading region" compared with a bar-shaped one, and induces a relatively higher bottleneck passing capacity in a walking passageway.